Cimbicidae (Hymenoptera, ‘Symphyta’) in the Paleogene: revision, the new subfamily Cenocimbicinae, and new taxa from the Eocene Okanagan Highlands - Archibald, S. Bruce; Rasnitsyn, Alexandr P. (Zootaxa, 2023)
We erect the Cenocimbicinae, a new subfamily of Cimbicidae (Hymenoptera, Symphyta), restricted to the Selandian Menat Formation of France, the oldest occurrence of the family, and the Ypresian Okanagan Highlands of far-western North America. We describe new taxa from the Okanagan Highlands: Allenbycimbex morrisae gen. et sp. nov. and Leptostigma n. gen. with seven new species: L. alaemacula n. sp., L. brevilatum n. sp., L. fasciatum n. sp., L. longiclava n. sp., L. longipallidum n. sp., L. longitenebricum n. sp., and L. proxivena n. sp. We revise the Cimbicidae from the Ypresian Green River Formation and the Priabonian Florissant Formation, both in Colorado, USA. The oldest fossil of a modern cimbicid subfamily appears with a single pachylostictine specimen in the Green River Formation, and all Cimbicidae are in modern subfamilies after the Ypresian (we did not examine one larva known from Priabonian Baltic amber). Pseudocimbex clavatus Rohwer 1908 from the Florissant Formation is not a cimbicid; we treat it as Tenthredinoidea incertae sedis. We transfer Cimbex vetusculus Cockerell to Floricimbex n. gen.